THE EFFECT OF IONIZING RADIATION ON URANOPHANE - Utsunomiya S.; Wang L.-M.; Ewing R.C.; Douglas M.; Clark S.B. (My University, 2003)
The susceptibility of uranophane, a uranyl sheet silicate, ideally Ca(UO2)2(SiO3OH)2(H2 (H2O)5, to ionizing irradiation has been evaluated by systematic irradations with 200 ke V electrons over the temperature range 94 to 573 K. High-resolution transmission electron microscopy revealed that amorphous domains formed locally, concurrently with a gradual disordering of the entire structure. Amorphization doses at room temperature were 1.1 × 1010 Gy for uranophane, 1.3 × 1010 Gy for Sr-substituted uranophane, and 1.9 × 1010 Gy for Eu-substituted uranophane; thus, there was an increase in amorphization dose with increasing average atomic mass. At 573 K, the amorphization dose of uranophane was 2.0 × 1011 Gy. The temperature dependence of the amorphization dose of uranophane has two stages; ≤413 K and >413 K. Based on a defect accumulation model, the effective activation energies for amorphization at each stage are 0.0440 eV and 0.869 eV, respectively. This suggests that the presence of H2O (and OH-) reduce the energy deposition required to cause amorphization. Above 413 K, the amorphization dose increased due to the absence of H2O and OH- and the absence of radiolytic decomposition of H2O and OH-.
Keywords: Uranophane